Problem-based learning as viewed by medical students in a non-problem based medical curriculum - Muhammad, Siti Aeshah @ Naznin; Syed Ahmad, Pakeer Oothuman; Abdullah, Nasuruddin; Jantan, Abdul Wahab (Blackwell Publishing Ltd, 2010)
The Medical Faculty of the International Islamic University Malaysia runs an undergraduate medical programme which implements a combination of traditional and new medical curricular trends. Problem based learning (PBL) is one of the teaching-learning approaches used in the preclinical years. This study analyses the effectiveness of PBL from the preclinical and clinical students perspective. Survey questionnaires were distributed to 196 Phase 1- preclinical (Years 1, 2) and 91 Phase 2-clinical (Year 3) students of academic session 2006/2007. The questionnaire consisted of 33 items assessing different aspects of PBL. Results showed that 86.4% of students agreed that PBL sessions achieved its aims of preparing students for the clinical years. Approximately 80% felt that the facilitators fulfilled their roles well. Thirty percent (59) of preclinical students indicated that they do not look forward to the PBL sessions. Only one third (60) of the preclinical students would like to have more PBL sessions. Sixty percent (55) of the clinical students however suggested that more PBL sessions be included in preclinical years as they found the experience beneficial in clinical years. Preclinical students however preferred lecture- based approach to PBL. Areas of concern relating to PBL included difficulty in: generating active discussion; confining oneself to specific tasks; lack of motivation, dominating facilitators, lack of confidence regarding the knowledge of peers and PBL cases constructed not based on real clinical scenarios. Our conclusion is that PBL is an effective study strategy in our non-problem based curriculum.